Pericardial Involvement in ST-Segment Elevation Myocardial Infarction as Detected by Cardiac MRI - Massalha, Eias; Brodov, Yafim; Oren, Daniel; Fardman, Alex; Natanzon, Sharon Shalom; Mazin, Israel; Beinart, Roy; Goldkorn, Ronen; Konen, Eli; Segni, Elio Di; Segev, Amit; Beigel, Roy; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Post myocardial infarction pericarditis (PMIP) is considered relatively rare in the current reperfusion era. The true incidence of PMIP may be underestimated since the diagnosis is usually based on clinical and echocardiographic parameters. Objectives: This study aims to document the incidence, extent, and prognostic implication of pericardial involvement in ST-elevation myocardial infarction (STEMI) using cardiac MRI (CMR). Methods: 187 consecutive ST-elevation myocardial infarction patients underwent CMR on day 5±1 following admission, including steady-state free precession (SSFP) and late Gadolinium enhancement (LGE) sequences. LGE and microvascular obstruction (MVO) was quantified as a percentage of left ventricular mass. LGE was graded for transmurality according to the 17 AHA left ventricle segment model (LGE score). Late pericardial enhancement (LPE), the CMR evidence of pericardial involvement, was defined as enhanced pericardium in the LGE series. LPE was documented adjacent to the left ventricle, the right ventricle, and both atria. Clinical, laboratory, angiographic, and echocardiographic data were collected. Clinical follow-up for major adverse cardiac events (MACE) was documented and correlated with CMR indices, including LGE, MVO, and LPE. Results: Late pericardial enhancement (LPE+) was documented in 77.5% of the study cohort. A strong association was found between LPE and the degree and extent of myocardial injury (LGE, MVO). Both LGE and MVO were significantly correlated with increased MACE on follow-up. On the contrary, LPE presence, either adjacent to the left ventricle or the other cardiac chambers, was associated with a lower MACE rate in a median of three years of follow-up HR 0.39, 95% CI (0.21-0.7), p=0.002, and HR 0.48, 95% CI (0.26-0.9), p=0.02, respectively. Conclusions: PMIP was documented by CMR in 77.5% of our STEMI cohort. Late pericardial enhancement presence correlated significantly with the extent and severity of the myocardial damage. Unexpectedly, it was associated with a considerably lower major adverse events rate in the follow-up period. Keywords: ST-Elevation Myocardial Infarction, Post Myocardial Infarction Pericarditis, Cardiac MRI, Microvascular Obstruction, Late Gadolinium Enhancement, Late Pericardial Enhancement